KEANEKARAGAMAN HAYATI TANAMAN LUMUT (BRYOPHITHA) DI HUTAN SEKITAR WADUK KEDUNG BRUBUS KECAMATANPILANG KECENG KABUPATEN MADIUN - Tiara Kusuma Wati; Bekti Kiswardianta; Ani Sulistyarsi (UNIVERSITAS PGRI MADIUN, 2016)
The aim of research to determine the diversity of plant species of moss in the forest areas around the reservoir Kedung Brubus Pilang Kenceng District of Madison County , based on the external structure and taxonomy , as the building blocks of high school biology lab manual mosses ( Bryophyta ) .Teknik research exploration , consisting of 6 points location as a decision mosses around the reservoir Kedung Brubus . Moss plants were found to be observed , identified, noted habitat , research location on the chart observations , documented and made herbarium . The results of the study there are 10 species Leucophanes glaucum, Thiudium investa, Polytrichum commune, Garovaglia plicata, Chenidium lychnites, Meteorium miquelianum, ricissa sp, Pogonotum cirrhatum, Fissidens cristatus, Barbrlla enervis.